Electrospun Fenoprofen/Polycaprolactone @ Tranexamic Acid/Hydroxyapatite Nanofibers as Orthopedic Hemostasis Dressings - Chang Huang; Menglong Wang; Siyou Yu; Deng-Guang Yu; Sim Wan Annie Bligh (Nanomaterials, 2024)
Dressings with multiple functional performances (such as hemostasis, promoting regeneration, analgesia, and anti-inflammatory effects) are highly desired in orthopedic surgery. Herein, several new kinds of medicated nanofibers loaded with several active ingredients for providing multiple functions were prepared using the modified coaxial electrospinning processes. With an electrospinnable solution composed of polycaprolactone and fenoprofen as the core working fluid, several different types of unspinnable fluids (including pure solvent, nanosuspension containing tranexamic acid and hydroxyapatite, and dilute polymeric solution comprising tranexamic acid, hydroxyapatite, and polyvinylpyrrolidone) were explored to implement the modified coaxial processes for creating the multifunctional nanofibers. Their morphologies and inner structures were assessed through scanning and transmission electron microscopes, which all showed a linear format without the discerned beads or spindles and a diameter smaller than 1.0 μm, and some of them had incomplete core–shell nanostructures, represented by the symbol @. Additionally, strange details about the sheaths’ topographies were observed, which included cracks, adhesions, and embedded nanoparticles. XRD and FTIR verified that the drugs tranexamic acid and fenoprofen presented in the nanofibers in an amorphous state, which resulted from the fine compatibility among the involved components. All the prepared samples were demonstrated to have a fine hydrophilic property and exhibited a lower water contact angle smaller than 40° in 300 ms. In vitro dissolution tests indicated that fenoprofen was released in a sustained manner over 6 h through a typical Fickian diffusion mechanism. Hemostatic tests verified that the intentional distribution of tranexamic acid on the shell sections was able to endow a rapid hemostatic effect within 60 s.